Enacting Woundedness and Compassionate Care for Recurrent Metastatic Breast Cancer. (January 2022) - Beach, Wayne A.
This analysis integrates Arthur Frank's timeless revelations about woundedness within the communication context of an oncology interview. A Patient whose life is threatened by recurrent metastatic breast cancer claims personal knowledge and visibly demonstrates impacts from illness experiences. Conversation Analysis (CA) was conducted on a video recorded and transcribed case study involving a Patient, her husband, and co-present oncologists. By focusing on narratives as talk-in-interaction, grounded exemplars are provided of primary interactional achievements: How woundedness gets displayed and responded to with empathy and compassionate witnessing; Patient's flooding out with emotion and potential embarrassment; attempting to regain control and resume talking about her condition; and the serial organization of crying and laughter when managing noticeably delicate moments. In this interview, woundedness is not discounted or dismissed but recognized as legitimate suffering meriting shared commiseration. Understanding how to enact humane and communicatively competent skills during emotionally uncertain moments can enhance medical education.